2006
DOI: 10.1016/j.jvs.2006.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of renal function after endovascular aneurysm repair with different transrenally fixated endografts

Abstract: Transrenal endograft fixation results in little deterioration in renal function during intermediate follow-up. The few patients who do experience a decline in renal function do so independently of any features related to the initial endovascular repair, and there is no difference in renal deterioration between endografts with nitinol and stainless steel transrenal bare metal stents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Here, renal impairment is commonly defined as a reduction of the preoperative eGFR by >20%. 4,9,10,21 In our study, the RIFLE consensus 17 was used to define and to classify ARF. CKD was described according to the clinical practice guidelines for CKD of the National Kidney Foundation, 14 applying the MDRD formula, and defined as an eGFR <60 mL/ min/1.73 m 2 for >3 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, renal impairment is commonly defined as a reduction of the preoperative eGFR by >20%. 4,9,10,21 In our study, the RIFLE consensus 17 was used to define and to classify ARF. CKD was described according to the clinical practice guidelines for CKD of the National Kidney Foundation, 14 applying the MDRD formula, and defined as an eGFR <60 mL/ min/1.73 m 2 for >3 months.…”
Section: Discussionmentioning
confidence: 99%
“…Reported renal insufficiency rates after OR and EVAR are similar, ranging from 13.9% to 17% 3 and 5% to 20%, [4][5][6] respectively. Several studies 2,4,5,[7][8][9][10][11][12] have reported that endografts with both suprarenal and infrarenal fixation are associated with a similar incidence of postoperative renal impairment.…”
mentioning
confidence: 99%
“…In the early part of the decade, the most common endografts used were Talent and Zenith reflecting our preference for transrenally fixated endografts, 9 whereas in the latter part of the decade, other transrenally fixated endografts with active fixation, including Endurant and Zenith, have been used in the majority of cases. This information is summarized in Fig 3. …”
Section: Overmentioning
confidence: 99%
“…A "clamp and pull" complete endograft extraction approach has been advocated by some surgeons; 2 however, this is a dangerous approach with transrenal fixated endografts, as the bare metal stent becomes incorporated into the juxtarenal aortic lining with a layer of neointima. 12 Endograft extraction with this technique can lead to clinically important tears in the pararenal aorta with hemorrhage and renal artery injury requiring revascularization. 5 Others have reported successful complete extraction by collapsing the upper bare metal stent into a large syringe 13 or by constricting it with a circumferential nylon tape or heavy suture.…”
Section: Researchmentioning
confidence: 99%